2013
DOI: 10.1177/0022034513502204
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-enhanced Derivation of iPSCs from Human Dental Pulp Cells

Abstract: Hypoxia enhances the reprogramming efficiency of human dermal fibroblasts to become induced pluripotent stem cells (iPSCs). Because we showed previously that hypoxia facilitates the isolation and maintenance of human dental pulp cells (DPCs), we examined here whether it promotes the reprogramming of DPCs to become iPSCs. Unlike dermal fibroblasts, early and transient hypoxia (3% O2) induced the transition of DPCs to iPSCs by 3.3- to 5.1-fold compared with normoxia (21% O2). The resulting iPSCs closely resemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…Although not observed in vivo, E-cadherin is expressed in cultured pulp cells (32). In this study, odontoblastic MDPC-23 cells showed opposite patterns in the expression of Nfic/E-cadherin and TGF-␤/N-cadherin.…”
Section: Discussioncontrasting
confidence: 51%
“…Although not observed in vivo, E-cadherin is expressed in cultured pulp cells (32). In this study, odontoblastic MDPC-23 cells showed opposite patterns in the expression of Nfic/E-cadherin and TGF-␤/N-cadherin.…”
Section: Discussioncontrasting
confidence: 51%
“…RNA extraction (RNeasy Plus Mini Kit; Qiagen) and RT-PCR (Thermal Cycler Dice Real Time System TP800; Takara, Shiga, Japan) were performed as described previously [3] [4] [18] . The mRNA data were normalized to those of GAPDH and used to calculate expression coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…E-cadherin and N-cadherin, both expressed in pulp cells during odontogenesis, are involved in the regulation of various biological processes, such as cell recognition, intercellular communication, cell fate, cell polarity, boundary formation, and morphogenesis [ 36 , 37 ]. In NFI-C −/− mice, KLF4 mRNA expression is significantly decreased compared to wild-type cells.…”
Section: Discussionmentioning
confidence: 99%